UNDANG-UNDANG CIPTA KERJA KLUSTER INDUSTRI PERTAHANAN DITINJAU DARI ARAH POLITIK HUKUM NASIONAL - Arjuna Al Ichsan Siregar (Media Keadilan: Jurnal Ilmu Hukum, 2021)
The DPR and the Government have approved the Law (Law) No. 11 of 2020 regarding job creation (Job Creation Law) on October 5, 2020. The ratification of this law has invited pros and cons and has drawn a lot of criticism and rejection. One of them is related to the issue of involving private business entities and foreign investment in the national defense industry by amending several articles in Law no. 16 of 2012. The author wants to examine the impact of involving private business entities and foreign investment in the national defense industry on the direction of national legal politics and how to solve them. The discussion in this research uses a normative juridical research model through data collection methods with literature searches and a legal regulatory approach. The data used is secondary data. The results of the study show that the involvement of privately-owned enterprises and foreign investment in the national defense industry is a serious and real threat and is contrary to the direction of achieving state goals within the framework of national legal politics. It is necessary to improve the job creation law for defense industry clusters by means of simultaneous improvements through the process of drafting regulations derived from the job creation law as well as through legislative review.Keywords: Job Creation Law; Defense Industry; National Law PoliticsAbstrakDPR dan Pemerintah telah menyetujui Undang-Undang No. 11 Tahun 2020 terkait penciptaan lapangan kerja (UU Cipta Kerja) pada tanggal 5 Oktober 2020. Pengesahan UU ini telah mengundang pro-kontra serta menuai banyak kritikan dan penolakan. Salah satunya terkait persoalan pelibatan badan usaha swasta dan investasi asing dalam industri pertahanan nasional dengan turut diubahnya beberapa pasal di UU No. 16 Tahun 2012. Penulis hendak mengkaji terkait dampak pelibatan badan usaha swasta dan investasi asing dalam industri pertahanan nasional terhadap arah politik hukum nasional serta bagaimanakah solusinya. Pembahasan dalam riset ini memakai model penelitian yuridis normatif melalui metode pengumpulan data dengan penelusuran kepustakaan serta pendekatan peraturan per-UU-an. Data yang digunakan adalah data sekunder. Hasil penelitian menunjukkan pelibatan badan usaha milik swasta dan investasi asing pada industri pertahanan nasional merupakan ancaman yang serius dan nyata serta bertentangan dengan arah pencapaian tujuan negara dalam kerangka politik hukum nasional. Perlu dilakukan perbaikan terhadap UU Cipta Kerja kluster industri pertahanan dengan cara perbaikan secara simultan melalui proses penyusunan regulasi turunan UU Cipta Kerja serta melalui jalur legislative review.